Use of Lidocaine 2% Gel Does Not Reduce Pain during Flexible Cystoscopy and Is Not Cost-Effective - Cano-Garcia, Maria del Carmen; Casares-Perez, Rosario; Arrabal-Martin, Miguel; Merino-Salas, Sergio; Arrabal-Polo, Miguel Angel (Urology Journal, 2015)
Purpose: To compare the use of lubricant gel with lidocaine versus lubricant gel without anesthetic in flexible cystoscopy in terms of pain and tolerability. Materials and Methods: In this observational non-randomized study, 72 patients were divided into two groups. Group 1 included 38 patients in whom lidocaine gel 2% was used and group 2 included 34 patients in whom lubricant gel without anesthetic was administered. The main variables analyzed were score in visual analogue scale (VAS) and score in Spanish Pain Questionnaire (SPQ). Student's t-test and Chi-square test were used to compare differences between 2 groups. The P values < .05% were considered statistically significant. Results: Mean age of patients in group 1 was 64.50 ± 12.39 years and 67.79 ± 10.87 years in group 2 (P = .23). The distribution according to sex was 29 men and 9 women in group 1 and 25 men and 9 women in group 2 (P = .78). The total VAS score was 2.21 ± 2.05 in group 1 versus 1.59 ± 1.61 in group 2 (P = .16). In the SPQ, the current intensity value was 1.82 ± 0.86 in group 1 versus 1.53 ± 0.74 in group 2 (P = .14), and the total intensity value was 1.92 ± 1.86 in group 1 versus 1.03 ± 1.75 in group 2 (P = .04). The cost of gel with lidocaine is 1.25 euro and gel without anesthetic 0.22 euro. Conclusion: The use of lidocaine gel does not produce benefit in terms of pain relief in flexible cystoscopy and also is costly.